Daily and seasonal variation of muscid flies (Diptera: Muscidae) in Chiang Mai province, northern Thailand - Tunwadee Klong-klaew (2020)
© 2020 Elsevier B.V. Flies of the family Muscidae, or muscids, are of medical and veterinary importance worldwide due to their recognition as nuisance pests and myiasis-producing agents. Effective control of muscids requires biological information on population dynamics daily and across seasons. In this study, such patterns were investigated in three different microhabitats (e.g., forest area, palm plantation and longan orchard) in a suburban area of Chiang Mai Province, northern Thailand. Adult fly samplings were conducted for 24-h intervals using semiautomatic traps and 1-day old beef offal as bait. Samplings were carried out twice per month from July 2013 to June 2014. A total of 3,419 muscids were trapped, comprising nine species, with Musca domestica Linnaeus accounting for the majority (n = 1,329; 38.9%) followed by Hydrotaea spinigera Stein (n = 770; 22.5%) and Musca ventrosa Wiedemann (n = 740; 21.7%). The greatest overall abundance was in the longan orchard location (n = 1,508; 44.1%). Community structure peaked during the rainy season (mid-May to mid-Oct). Peak activity during the day was late morning (9.00 to 12.00 h) for M. domestica, early morning (6.00 to 9.00 h) for H. spinigera, and early afternoon (12.00 to 15.00 h) for M. ventrosa. Temperature had no significant effect on the abundance of M. domestica (rs= -0.030, p = 0.576) or H. spinigera (rs = 0.068, p = 0.200), but had a weak negative correlation with M. ventrosa (rs = −0.238, p = 0.0001). Relative humidity had a weak negative correlation with M. domestica (rs = −0.263, p = 0.0001), H. spinigera (rs = −0.107, p = 0.043) and M. ventrosa (rs = −0.344, p = 0.0001). More females (n = 2,078) were trapped than males (n = 761). These results provide baseline information of daily and seasonal dynamic activity of muscid flies under natural conditions, which is the prerequisite information for effective control measures.